Developing in-house library software application: University of Ibadan library integrated software (UI-ILS) (2019)
Purpose: The study was carried out to examine the library integrated software compatibility, usage and application in University of Ibadan, with the sole aim of highlighting the utilization and potentials of Library Integrated software and its practical importance to Kenneth Dike Library. Implications: The study also established that the library management need to embark on sensitization programme in order to create awareness among professional and paraprofessional librarians concerning usage and application of these varied software to boost provision of library services to users. Originality/Value: It was recommended that existing software need to be improve and upgrade to boost service provision and that the library management also need to embark on routine training for professionals and paraprofessional librarians on emerging technology such as library software.